Design of Quad-Band Rat-Race Coupler for GSM/WiMAX/WLAN/Satellite Applications - Althuwayb, Ayman A. (Společnost pro radioelektronické inženýrství, 2021)
In this communication, a novel quad-band rat-race coupler (RRC) is developed for GSM/WiMAX/WLAN/Satellite applications. A conventional RRC is converted to exhibit quad-band operation by using a quad-band microstrip-line (QBML). The proposed QBML is constructed by two coupled-lines, one series transmission-line and two short-ended stubs. The ABCD matrix method is applied to develop the design formulas. Based on these formulas, a quad-band RRC operating at 1.8 GHz, 3.5 GHz, 5.4 GHz, and 7.1 GHz is designed and verified through fabrication and measurement. The measurement and full-wave simulation responses are very much consistent as expected.
Keywords: Rat-race coupler; quad-band; coupled-line